Cell labeling approaches for fluorescence-based in vivo flow cytometry - Runnels, Judith M.; Spencer, Joel A.; Pitsillides, Costas; Zhi, Liang; Wu, Mei X.; Lin, Charles P. (My University, 2011)
We provide an overview of the methods used to label circulating cells for fluorescence detection by in vivo flow cytometry. These methods are useful for cell tracking in small animals without the need to draw blood samples and are particularly useful for the detection of circulating cancer cells and quantification of circulating immune cells
Keywords: Cell tracking; Circulating immune cells; Circulating tumor cells; In vivo flow cytometry